2016
DOI: 10.1039/c5sc03694a
|View full text |Cite
|
Sign up to set email alerts
|

Electronic control of DNA-based nanoswitches and nanodevices

Abstract: Here we demonstrate that we can rationally and finely control the functionality of different DNA-based nanodevices and nanoswitches using electronic inputs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
46
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 51 publications
(46 citation statements)
references
References 60 publications
0
46
0
Order By: Relevance
“…We employed square wave voltammetry (SWV; Supporting Information, Figure S4), which quantitatively suggested that about 20 mm of Cu 2+ was electrochemically released from the electrode. [22] The absence of NP precipitation and/or aggregation was proven by a combination of UV/Vis spectroscopy, DLS and TEM analyses, confirming that Au NP 1 is stable under the release conditions ( Supporting Information, Figures S6-S8). Kinetic measurements (Figure 2) of the initial rate of HPNPP transphosphorylation confirmed that the catalytic system achieved the same activity after the electrochemical release of Cu 2+ (v init = 7.4(AE 1.2) 10 À9 m s À1 ) as compared to manual addition (v init = 7.7(AE 1.2) 10 À9 m s À1 ).…”
mentioning
confidence: 61%
See 2 more Smart Citations
“…We employed square wave voltammetry (SWV; Supporting Information, Figure S4), which quantitatively suggested that about 20 mm of Cu 2+ was electrochemically released from the electrode. [22] The absence of NP precipitation and/or aggregation was proven by a combination of UV/Vis spectroscopy, DLS and TEM analyses, confirming that Au NP 1 is stable under the release conditions ( Supporting Information, Figures S6-S8). Kinetic measurements (Figure 2) of the initial rate of HPNPP transphosphorylation confirmed that the catalytic system achieved the same activity after the electrochemical release of Cu 2+ (v init = 7.4(AE 1.2) 10 À9 m s À1 ) as compared to manual addition (v init = 7.7(AE 1.2) 10 À9 m s À1 ).…”
mentioning
confidence: 61%
“…[21] Finally, Cu 2+ and Cd 2+ metal ions were chosen for their different standard reduction potentials (respectively À0.40 and + 0.34 V for Cd 2+ and Cu 2+ , relative to the standard hydrogen electrode). [22] We focused our initial investigations on the electrochemical generation of metal ions from a source in order to switch on catalytic activity. To that purpose, we used a carbon chip [23] previously coated with a film of Cu 0 .…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…It has already been demonstrated that DNA molecular machines can be controlled using electrical signals, using electrochemical control of pH and pH-sensitive structures such as imotifs or triplexes 14,15 or electronically triggered release of a signalling species from a surface 16 . In an alternative architecture, an enzymatic logic gate under certain conditions produces NADH, which activates an electrochemical process that leads to release of DNA from an alginate matrix 17 .…”
Section: Introductionmentioning
confidence: 99%
“…For example, sequences of DNA are rationally designed to recognize a specific target molecule and convert the recognition event into a useful function (i.e., signal production or release of a cargo) . Despite the great advantages represented by such nanodevices, their target‐induced actuation is usually achieved by exogenously adding them into a sample . To make a better control of activating DNA‐based nanodevices, we need to find a precisely controllable way out of common basic mechanism.…”
Section: Introductionmentioning
confidence: 99%